INVITRO CITOTOXICITY ASSAYS OF SEAGRASS (Enhalus acoroides) METHANOL EXTRACT FROM SOROPIA COASTAL WATERS SOUTHEAST SULAWESI REGENCY - Theosobia Grace Orno; Agnes Rantesalu (Universitas Nahdlatul Ulama Surabaya, 2020)
The studies analysing the use of natural ingredients as an alternative treatment in the field of pharmacology are developing very rapidly. One of researches that is quite promising in the pharmaceutical industry is the application of marine materials. Marine materials that are frequently used consist of shellfish, algae, sponges and seagrass. Several studies on toxicity tests have shown that the methanol extract of seagrass (from species Enhalus acoroides) is more toxic than the other seagrass family. This study aims to test the toxicity level of Seagrass (E. acoroides) extract from Soropia coastal waters. The research method in this study was an experimental laboratory using E. acoroides Seagrass as a sample that was obtained from Soropia Coast, Konawe Regency, Southeast Sulawesi Province. The sample was extracted using methanol as a solvent by macerating it and was tested for its toxicity using the Brine Shrimp Lethality Test (BSLT) method. Toxicity test results showed that the samples with a concentration of 10 ppm, 100 ppm and 1000 ppm in leaves extracts produced an LC50 value of 404.88 ppm, while the stem and root extracts has a value of LC50 >1000 ppm. The test was continued with higher concentration of leaves extracts consisted of 250 ppm, 500 ppm, and 1000 ppm. The toxicity test showed an LC50 value of 0.7309; which means that it was very toxic. The methanol extract of Seagrass (E. Acoroides) is potential to be used for further analysis and anticancer formulations.